Analisis Pengaruh E-Sport Tourism pada Pokemon Go Terhadap Peningkatan Wisatawan di Kabupaten Tangerang - Sarudin, Rendy; Hakim, Bhustomy (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine the influence of the E-Sport Tourism game Pokemon Go on Interest in Visiting Tangerang Regency through the Tangerang Serpong Raider Community. The results of this research show that: (1) if E-sports tourism in Pokemon Go is equal to zero (0), then the increase in tourists in Tangerang Regency will be 7,178 as evidenced by the constant value obtained which is 7,178. (2) E-sports Tourism in Pokemon Go positively influences increasing tourists in Tangerang Regency as evidenced by the regression coefficient value of 0.600. (3) E-sports Tourism in Pokemon Go influences the number of tourists by 60.0% while the remaining 40.0% is influenced by other variables as evidenced by the R square result which is 0.600.